Transient expression of gene encoding ZmLEA14A protein in Nicotiana benthamiana plant - Hong Hanh, Ha; Hien, Le Thi Thu; Thi Thu Hue, Huynh (Vietnam Journal of Biotechnology, 2020)
LEA protein family includes proteins accumulated in the late stage of embryogenesis and in vegetative tissues of stress-confronted plant. These proteins have been demontrated to play a major role in plant response to abiotic stresses, such as drought and salinity stress. The genes coding for LEA proteins in maize are divided into 9 groups including LEA 1, LEA 2, LEA 3, LEA 4, LEA 5, LEA 6, SMP, dehydrin, and AtM. The application of LEA genes to improve drought tolerance for plants by genetic engineering has also been studied extensively all over the world. In this study, pCAM/35S-ZmLEA14A-35S vector and pCAM/Ubi-ZmLEA14A-35S vector contained the ZmLEA14A gene isolated from Te vang 1, these vectors were used to transient express into Nicotiana benthamiana tobacco leaves by agro-infiltration method. The results of immunoassay between cmyc specific antibodies with proteins from infected leaves revealed the expression of recombinant ZmLEA14A protein in N. benthamiana leaves. Thereby, two constructs habouring the ZmLEA14A gene work at transcription and translation levels in the model plant that could harnessed for stable transformation in plants.